Persistent RNA virus infection of lepidopteran cell lines: Interactions with the RNAi machinery. (October 2016) - Swevers, Luc; Ioannidis, Konstantinos; Kolovou, Marianna; Zografidis, Aris; Labropoulou, Vassiliki; Santos, Dulce; Wynant, Niels; Broeck, Jozef Vanden; Wang, Luoluo; Cappelle, Kaat; Smagghe, Guy
Graphical abstract: Highlights: Broad infectivity of lepidopteran cell lines by RNA viruses. Sf21 and Hi5-SF cells as models to study the impact of RNA virus infection on RNAi. Minimal impact of virus infection on RNAi efficiency in 2 types of reporter assays. Clearance of RNA virus infection by RNA hairpin in Hi5 cells. Intact ORF of RNAi inhibitor in RNA virus genomes. Abstract: RNAi is broadly used as a technique for specific gene silencing in insects but few studies have investigated the factors that can affect its efficiency. Viral infections have the potential to interfere with RNAi through their production of viral suppressors of RNAi (VSRs) and the production of viral small RNAs that can saturate and inactivate the RNAi machinery. In this study, the impact of persistent infection of the RNA viruses Flock house virus (FHV) and Macula-like virus (MLV) on RNAi efficiency was investigated in selected lepidopteran cell lines. Lepidopteran cell lines were found to be readily infected by both viruses without any apparent pathogenic effects, with the exception of Bombyx -derived Bm5 and BmN4 cells, which could not be infected by FHV. Because Sf21 cells were free from both FHV and MLV and Hi5-SF were free from FHV and only contained low levels of MLV, they were tested to evaluate the impact of the presence of the virus. Two types of RNAi reporter assays however did not detect a significant interference with gene silencing in infected Sf21 and Hi5-SF cells when compared to virus-free cells. In Hi5 cells, the presence of FHV could be easily cleared through the expression of an RNA hairpin that targets its VSR gene, confirming that the RNAi mechanism was not inhibited. Sequencing indicated that the B2 RNAi inhibitor gene of FHV and a putative VSR gene from MLV were intact in persistently infected cell lines, indicating that protection against RNAi remains essential for virus survival. It is proposed that infection levels of persistent viruses in the cell lines are too low to have an impact on RNAi efficiency in the lepidopteran cell lines and that encoded VSRs act locally at the sites of viral replication (mitochondrial membranes) without affecting the rest of the cytoplasm.